PTU-009 The utility of routine chromoendoscopy for detection of dysplastic lesions during surveillance colonoscopy in patients with colonic inflammatory bowel disease. does research translate to clinical practice?. (22nd June 2015) - Mohammed, N; Javaid, U; Thethi, R; Luthra, P; Hamlin, J; Rembacken, B; Subramanian, V
Abstract : Introduction: Dysplasia in colonic inflammatory bowel disease (IBD) is often multifocal and flat. Chromoendoscopy (CE) has been shown in prospective studies to improve dysplasia detection rates by improving the ability to detect subtle mucosal changes. 1 The utility of CE in dysplasia detection in patients with IBD during routine clinical practice has not been reported so far. We aimed to compare the yield of dysplastic lesions detected by CE with standard white light endoscopy (WLE). Method: Retrospective cohort study of patients with long standing (>7 years) colonic IBD undergoing surveillance colonoscopy at Leeds Teaching Hospital NHS Trust between January 2012 to December 2013. Details of diagnosis, duration of disease and outcomes of the colonoscopy were collected from the endoscopy database, electronic patient records and patient notes. Results: There were 120 colonoscopies in the CE group and 220 colonoscopies in the WLE group. The groups were well matched for all demographic variables. 27 dysplastic lesions were detected in 20 patients in the CE group and 9 dysplastic lesions were detected in 6 patients in the WLE group. All the lesions were detected on targeted biopsy and harboured low grade dysplasia. The adjusted prevalence ratio (on a per patient basis) for detecting any dysplastic lesion was 4.6 (95% CI 1.6–13.7) in favour of CE. Conclusion: CE colonoscopy improves detection of dysplastic lesions during surveillance colonoscopy of patients with colonic IBD even in routine clinical practice, confirming data from prospective trials. CE should be the standard of care for all IBD surveillance procedures as advocated by both BSG and ECCO guidelines. Disclosure of interest: None Declared. Reference: Subramanian V, Mannath J, Ragunath K, et al . Meta-analysis: the diagnostic yield of chromoendoscopy for detecting dysplasia in patients with colonic inflammatory bowel disease. Aliment Pharmacol Ther. 2011;33(3):304–12